2012
DOI: 10.1111/j.1462-5822.2012.01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia type IV secretion effector ECH0825 is translocated to mitochondria and curbs ROS and apoptosis by upregulating host MnSOD

Abstract: Summary Ehrlichia chaffeensis infects monocytes/macrophages and causes human monocytic ehrlichiosis. To determine the role of type IV secretion (T4S) system in infection, candidates for T4S effectors were identified by bacterial two-hybrid screening of E. chaffeensis hypothetical proteins with positively charged C-terminus using E. chaffeensis VirD4 as bait. Of three potential T4S effectors, ECH0825 was highly upregulated early during exponential growth in a human monocytic cell line. ECH0825 was translocated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
138
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(140 citation statements)
references
References 88 publications
2
138
0
Order By: Relevance
“…Ehrlichia spp. other than E. canis have been shown to decrease reactive oxygen species capable of destroying intracellular pathogens, and inhibiting monocyte death by apoptosis (Liu et al, 2012). Both of these mechanisms potentially facilitate longer intracellular pathogen survival, nevertheless, other mechanisms may be involved in H. canis and E. canis co-infection.…”
Section: Discussionmentioning
confidence: 98%
“…Ehrlichia spp. other than E. canis have been shown to decrease reactive oxygen species capable of destroying intracellular pathogens, and inhibiting monocyte death by apoptosis (Liu et al, 2012). Both of these mechanisms potentially facilitate longer intracellular pathogen survival, nevertheless, other mechanisms may be involved in H. canis and E. canis co-infection.…”
Section: Discussionmentioning
confidence: 98%
“…However, Liu et al found that mitochondrial biochemical activity was reduced, as evidenced from the measurement of mitochondrial DNA synthesis or the transcription of several mitochondrial genes (37). There is also evidence that the E. chaffeensis type IV secretion system is used to insert bacterial effector proteins into host mitochondria (36). These observations suggest that the organism inhibits mitochondrial activity, perhaps to inhibit the generation of mitochondrially produced oxidative products that would be harmful to the bacteria (5,68).…”
Section: Discussionmentioning
confidence: 99%
“…marginale (Lockwood et al ., 2011) and E . chaffeensis (Rikihisa & Lin, 2010, Liu et al ., 2012) . To our knowledge, only two of these effectors have been shown to directly interact with their cognate RvhD4 proteins: Ats-1 of A .…”
Section: Sec-independent Secretory Pathwaysmentioning
confidence: 99%
“…phagocytophilum (Niu et al ., 2010) and ECH0825 of E . chaffeensis (Liu et al ., 2012) . All other rvh substrates, including the well-characterized AnkA effector, were shown to be translocated by heterologous T4SSs from either A .…”
Section: Sec-independent Secretory Pathwaysmentioning
confidence: 99%